Laparoscopic Sleeve Gastrectomy for Severe and Morbid Obesity: A Narrative Literature Review - Maharsi, Chiendo Yurinda; Huda Fajar Arianto; Willy Yulianto (Open Access Indonesian Journal of Medical Reviews, 2022)
The prevalence of severe and morbid obesity keeps increasing in significant value and has become a major problem around the world. Society itself, whether in young adult or senior, currently keep looking to manage them. The current effective and approved treatment for this condition is known as metabolic and bariatric surgery (MBS), in which there are several procedures, including laparoscopic sleeve gastrectomy. Even though knowledge regarding this procedure keeps evolving, the study found that the laparoscopic sleeve gastrectomy procedure brings minimal complication with quality-of-life improvement, especially in a cardiometabolic risk society. This review aims to further discuss the procedure definition, changes in diet, benefits, and obesity relapse in the future after this procedure.